The differences in acceleration, maximal speed and agility between soccer, basketball, volleyball and handball players - Simonek, J.; Horicka, P.; Hianik, J. (Journal of Human Sport & Exercise, 2017)
Complex reaction speed, acceleration, maximum speed, speed of whole-body change of direction and agility represent the basic components of sport performance mainly in sport games and combat sports. However, contradictory findings have been reported as to the extent of the relationship between the different speed and agility components. This study comprised 117 players (soccer - 56, basketball - 17, volleyball - 20, and handball - 24) playing youth leagues U15-U17 who were assessed for 10-m sprint (acceleration), flying 30-m sprint (maximum speed), triple-jump (special explosiveness) performance, Illinois agility test (speed of whole-body change of direction) and Fitro Agility Check (agility). Low (0.112-0.425 in soccer) correlation coefficients between the factors were found in soccer, while in the other sport games they were medium (0.329-0.623 in basketball; 0.414-0.686 in handball) to high (0.569-0.768 in volleyball). Negative relationship was observed between Triple jump and all other tests performances in all sports games. The findings suggest that specific training procedures for each speed and agility component should be utilized already in junior ages.